Problem Based Learning with Pop-Up Books to Enhance Reading Abilities Fiction Comprehension and Critical Thinking - Hilda Rinjani, Ilda; Wikanengsih (JLER (Journal of Language Education Research), 2025)
This research aims to investigate the challenges related to reading comprehension and critical thinking among elementary school students. Specifically, it examines the effectiveness of a pop-up book-assisted problem-based learning model in enhancing sixth-grade students' abilities to read, understand fictional stories, and think critically. Employing a mixed-methods approach with an exploratory sequential design, the study first conducted qualitative research, followed by quantitative research. Qualitative data were collected through observations of teachers and students, while quantitative data were gathered via tests. The qualitative phase yielded a positive outcome, demonstrating an 80% success rate in improving students' reading comprehension and critical thinking skills with the pop-up book-assisted model. The quantitative phase further revealed that students who used this model achieved reading comprehension and critical thinking scores exceeding the minimum completion criterion of 70. Mastery of reading, understanding, and critical thinking is crucial for elementary students as it prepares them for subsequent educational levels.